Modeling the black holes surrounded by a dark matter halo in the galactic center of M87 - Dong Liu; Yi Yang; Zhaoyi Xu; Zheng-Wen Long (European Physical Journal C: Particles and Fields, 2024)
Abstract In this paper, the structure of a dark matter halo can be well described by the mass model of M87 and the Einasto profile for the cold dark matter model, i.e., $$ρ _{\text {eina}} (r)=ρ _\text {e} \exp ( -2 α ^{-1} ((r/r_\text {e})^α -1 ) )$$ ρ eina ( r ) = ρ e exp ( - 2 α - 1 ( ( r / r e ) α - 1 ) ) (Wang et al. in Nature 585:39–42, 2020) . Under these conditions, we construct a solution of a static spherically symmetric black hole in a dark matter halo. Then, using the Newman–Janis algorithm, we extend this static solution to the case of rotation, and obtain a solution for the Kerr-like black hole. We prove that this solution of the Kerr-like black hole is indeed a solution to the Einstein field equations. Finally, taking M87 as an example, we study and analyze some physical properties of this Kerr-like black hole, and then compare them with the Kerr black hole. Particularly, from the perspective of the black hole shadow and the fact that the Kerr-like black hole and the Kerr black hole is distinguishable, we give the upper limit of the shape parameter of the Einasto density profile, that is approximately $$α <0.22$$ α < 0.22 , which may provide a new method to further improve and perfect the density profile of dark matter model. These research results for the black hole in a dark matter halo may indirectly provide an effective method for detecting the existence of dark matter.